2018
DOI: 10.1007/s10900-018-0486-0
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Provider Practices and Perceptions Regarding HPV Vaccination and Anal Cancer Screening at a Boston Community Health Center

Abstract: Human papillomavirus (HPV) vaccination and anal cancer screening are valuable, yet underutilized, tools in prevention of HPV-related cancers among sexual and gender minority (SGM) populations. The aim of this study was to characterize primary care providers' (PCPs) practices and perceptions pertaining to HPV vaccination and anal cancer screening. A survey assessing self-reported practice characteristics related to HPV vaccination and anal cancer screening, as well as perceived barriers to vaccination and anal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 44 publications
1
14
0
1
Order By: Relevance
“…Contributing factors for not identifying, screening, or referring at-risk patients may have been provider comfort level with discussing AC screening and performing anal cytology 14 providers’ unconfirmed assumptions regarding patients’ sexual orientation and practices, 15,16 and time constraints during clinic visits. 17 Consistent with our previous provider survey findings, male providers were less likely to refer their patients for screening, and the 2 highest referring providers to the clinic were female. 5 The lack of clinical trial data on the impact of AC screening adds uncertainty around the value of screening.…”
Section: Discussionsupporting
confidence: 87%
“…Contributing factors for not identifying, screening, or referring at-risk patients may have been provider comfort level with discussing AC screening and performing anal cytology 14 providers’ unconfirmed assumptions regarding patients’ sexual orientation and practices, 15,16 and time constraints during clinic visits. 17 Consistent with our previous provider survey findings, male providers were less likely to refer their patients for screening, and the 2 highest referring providers to the clinic were female. 5 The lack of clinical trial data on the impact of AC screening adds uncertainty around the value of screening.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have shown that the decreased risk of AC seen in Hispanics and Asians may be due to more access to HPV vaccines at early ages (16). Access to HPV vaccines at an early age decreases the likelihood of being infected with any strains associated with AC (11,12,17).…”
Section: Discussionmentioning
confidence: 99%
“…In the last five years in Turkey, the reported prevalences of cervical cancer, vulvar cancer, anal cancer and penile cancer were 16.09%, 1.82%, 1.09%, and 0.16%, respectively (7). HPV vaccine is a proven method for preventing HPV-related cancers and genital warts, especially preventing cervical cancer (8,9). It is reported that vaccines containing HPV16-18 types prevent 63% of all HPV-related cancers; vaccines containing nine types of HPV (HPV6-11-16-18-31-33-45-52-58) provide protection against cervical, vulvar, vaginal, and anal cancers by 90% (6,10).…”
Section: According To Data From the Surveillance Program Conducted Bymentioning
confidence: 99%